SPRY2 loss enhances ErbB trafficking and PI3K/AKT signalling to drive human and mouse prostate carcinogenesis - Gao, Meiling (WILEY-VCH Verlag, 2012)
Loss of SPRY2 and activation of receptor tyrosine kinases are common events in prostate cancer (PC). However, the molecular basis of their interaction and clinical impact remains to be fully examined. SPRY2 loss may functionally synergize with aberrant cellular signalling to drive PC and to promote treatment-resistant disease. Here, we report evidence for a positive feedback regulation of the ErbB-PI3K/AKT cascade by SPRY2 loss in in vitro as well as pre-clinical in vivo models and clinical PC. Reduction in SPRY2 expression resulted in hyper-activation of PI3K/AKT signalling to drive proliferation and invasion by enhanced internalization of EGFR/HER2 and their sustained signalling at the early endosome in a PTEN-dependent manner. This involved p38 MAPK activation by PI3K to facilitate clathrin-mediated ErbB receptor endocytosis. Finally, in vitro and in vivo inhibition of PI3K suppressed proliferation and invasion, supporting PI3K/AKT as a target for therapy particularly in patients with PTEN-haploinsufficient-, low SPRY2- and ErbB-expressing tumours. In conclusion, SPRY2 is an important tumour suppressor in PC since its loss drives the PI3K/AKT pathway via functional interaction with the ErbB system.